Moderation of Firm Size in the Influence of Working Capital and Inventory on the Company's Financial Performance - Shabihah, Khansa; Rusdi, Dedi (DINASTI RESEARCH, 2025)
This study analyzes the influence of Working Capital and Inventories on company performance with firm size as a moderation variable in non-financial companies in Indonesia for the 2003-2023 period. The regression results show that working capital and inventories have a significant influence on the company's performance, but this influence is influenced by the firm size. In the second model, firm size does not have a significant direct influence on company performance, but can moderate the relationship between Working Capital and Inventories with company performance. These findings indicate that although large companies tend to be more efficient in managing working capital and inventory, external factors and managerial policies also play an important role in determining company performance. The study advises companies to improve financial management and reduce agency problems by paying attention to the alignment of goals between owners and managers, as well as taking into account external dynamics that affect performance.